Islam, Education, And Nationalism: Exploring The Leadership Of Abu Daud Beureu’eh In Indonesian’s Independence Movement - Nuzula, Mukhsin; Heri Fajri; Junaidi Salat; Zetta Fazira (Jurnal Serambi Ilmu, 2025)
Abu Daud Beureu’eh, a charismatic scholar and politician from Aceh, played a crucial role in Indonesia’s independence struggle and the promotion of nationalism values, which remain relevant to current educational trends. The values of struggle and leadership exemplified by Abu Daud Beureu’eh offer valuable insights for integrating nationalism into Indonesia’s educational curriculum, particularly in cultivating students’ patriotism and integrity through localized historical narratives and moral values. The purpose of this study was to examine Abu Daud Beureu’eh’s contribution to the shaping of Indonesian nationalist education and to analyze his leadership style, which combines Islamic values with the spirit of nationalism. The research employs a qualitative approach with a historical research methodology, using data collection techniques such as literature review, interviews, and direct observation in Pidie Regency. Purposive sampling was used, and the data collection instruments included in-depth interviews. The research findings reveal that Abu Daud Beureu’eh’s leadership style incorporated various approaches which were effective in advancing the struggle for independence and building national awareness. The global implications of this research highlight the importance of integrating religious education with nationalism as a model for fostering national consciousness, which remains relevant in the context of globalization and the challenges of contemporary education.